2018
DOI: 10.1371/journal.pone.0205989
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparison of bleeding risks among non-valvular atrial fibrillation patients prescribed apixaban, dabigatran, or rivaroxaban

Abstract: Limited real-world data are available regarding the comparative safety of non-vitamin K antagonist oral anticoagulants (NOACs). The objective of this retrospective claims observational cohort study was to compare the risk of bleeding among non-valvular atrial fibrillation (NVAF) patients prescribed apixaban, dabigatran, or rivaroxaban. NVAF patients aged ≥18 years with a 1-year baseline period were included if they were new initiators of NOACs or switched from warfarin to a NOAC. Cox proportional hazards model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 32 publications
9
36
0
1
Order By: Relevance
“…in a US claims database also found that rivaroxaban had a worse safety profile than dabigatran and apixaban 23 . Similar observations have been made in other studies as well 27,29–31 . The difference found for rivaroxaban might be explained by selective prescribing of this drug to patients with higher stroke and bleeding risk.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…in a US claims database also found that rivaroxaban had a worse safety profile than dabigatran and apixaban 23 . Similar observations have been made in other studies as well 27,29–31 . The difference found for rivaroxaban might be explained by selective prescribing of this drug to patients with higher stroke and bleeding risk.…”
Section: Discussionsupporting
confidence: 79%
“…23 Similar observations have been made in other studies as well. 27,[29][30][31] The difference found for rivaroxaban might be explained by selective prescribing of this drug to patients with higher stroke and bleeding risk. Although the analysis was corrected for confounding, unobserved confounding could still be present.…”
Section: Resultsmentioning
confidence: 99%
“…Intracranial bleeding is considered the most prominent and potentially fatal complication in patients on oral anticoagulants [1,10]. As apixaban may have greater clinical benefits than acenocoumarol, this may have been accepted by physicians when selecting anticoagulant treatment [13][14][15]. Likewise, 77.5% of patients initiated apixaban at a dose of 10 mg/day, consistent with other studies [11,12].…”
Section: Discussionsupporting
confidence: 56%
“…In patients with NVAF, novel oral anticoagulants (NOACs) have demonstrated a better risk-benefit profile than VKA in clinical trials [10]. Available NOACs include dabigatran, rivaroxaban, apixaban and edoxaban [11][12][13][14][15]. No head-to-head clinical trials have compared NOACs, although observational studies suggest differences in the risk-benefit profile between them [11].…”
mentioning
confidence: 99%
“…AF in cancer patients may be a comorbid state due to their older age, disbalance of electrolytes, hypoxia, and age-related metabolic disorders, thus the link between AF and cancer may be due to the above-determined factors [19]. The comorbidity profiles were quite similar to apixaban, dabigatran, and rivaroxaban for bleedings and strokes [20].…”
Section: Atrial Fibrillation and Cancermentioning
confidence: 90%